Applicability of STWS Technique in Solving Linear System of Stiff Delay Differential Equations with Constant Delays - Dhayabaran*, A. Emimal Kanaga Pushpam and D. Paul (Recent Research in Science and Technology, 2011)
This paper presents the Single Term Walsh Series (STWS) technique to determine the numerical solution to stiff linear systems of delay differential equations (DDEs) with single and multiple constant delays. The applicability of this technique is demonstrated with examples of stiff delay systems. The discrete solutions obtained using the STWS technique is compared with their corresponding exact solutions.